2018
DOI: 10.1016/j.cbpb.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in teleost fish: From molecular mechanisms to physiological phenotypes

Abstract: While the field of epigenetics is increasingly recognized to contribute to the emergence of phenotypes in mammalian research models across different developmental and generational timescales, the comparative biology of epigenetics in the large and physiologically diverse vertebrate infraclass of teleost fish remains comparatively understudied. The cypriniform zebrafish and the salmoniform rainbow trout and Atlantic salmon represent two especially important teleost orders, because they offer the unique possibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 372 publications
(373 reference statements)
0
102
1
Order By: Relevance
“…The epigenetic molecular component of phenotypic variability in salmonids is relatively poorly understood but holds promise for translational research relevant to stock enhancement in aquaculture (for recent reviews, see Gavery & Roberts ; Best et al . ). In this respect, FAASG aims to exploit a range of well‐established technologies that enable profiling of DNA methylation, repressive and permissive histone modifications, chromatin accessibility and higher chromatin structure (Macqueen et al .…”
Section: State Of the Art And Perspectivesmentioning
confidence: 97%
“…The epigenetic molecular component of phenotypic variability in salmonids is relatively poorly understood but holds promise for translational research relevant to stock enhancement in aquaculture (for recent reviews, see Gavery & Roberts ; Best et al . ). In this respect, FAASG aims to exploit a range of well‐established technologies that enable profiling of DNA methylation, repressive and permissive histone modifications, chromatin accessibility and higher chromatin structure (Macqueen et al .…”
Section: State Of the Art And Perspectivesmentioning
confidence: 97%
“…Recent epigenetics studies have focused mostly on stable heritable phenotypes that result from structural changes in chromatin (e.g. DNA methylation or histone modification) without alternations in the DNA nucleotide sequence itself (Berger et al ., ; Best et al ., ). Although these changes can be self‐perpetuated over generations by the phenotypic outcome of epigenetic responses (Flores, Wolschin, & Amdam, ), some environmentally induced epigenetic modifications are repeatable across similar environments (Le Luyer et al ., ) and stably inherited across generations (Danchin, ).…”
Section: From the Inside Looking Out: Intrinsic Factors And Leveraginmentioning
confidence: 99%
“…Although these changes can be self‐perpetuated over generations by the phenotypic outcome of epigenetic responses (Flores, Wolschin, & Amdam, ), some environmentally induced epigenetic modifications are repeatable across similar environments (Le Luyer et al ., ) and stably inherited across generations (Danchin, ). Recent studies have identified differentially methylated regions associated with adaptive phenotypic variation in postglacial fishes (Best et al ., ), such as lateral plate morphs in three‐spined stickleback (Smith et al ., ), migration phenotypes in rainbow trout ( Oncorhynchus mykiss ) (Baerwald et al ., ) and the degree of behavioural reproductive isolation in tessellated darters ( Etheostoma olmstedi ) (Smith et al ., ). However, the frequency with which environmentally induced epigenetic variation is inherited is currently unknown (Smith & Ritchie, ) and we need to understand how stable heritable phenotypes that result from structural changes in chromatin may feed back to, and influence, genetic variation, ecology, and evolution.…”
Section: From the Inside Looking Out: Intrinsic Factors And Leveraginmentioning
confidence: 99%
“…However, such a clear association remains elusive in non-model fish species [46]. Moreover, most studies in marine fish, including those conducted in gilthead sea bream, have managed the ratio n-3-LC-PUFA/C18 PUFA, but have not yet consider the potential value of C18 PUFA alone as a nutritional programing tool [40,41,42].…”
Section: Introductionmentioning
confidence: 99%